ANALISIS EKSPERIMEN LAJU ALIRAN VOLUME AIR TERHADAP TEMPERATUR AIR PANAS PADA HEAT RECOVERY SISTEM AC JENIS WATER CHILLER - I Made Rasta (Dinamika Teknik Mesin, 2011)
Refrigerant in refrigeration machines will absorb heat from a room space and released the heat to the environment. The heat balancing in the system is heat released from condenser equal with heat absorbed from room space added by the heat equivalent from compressor work. Based on this heat cycle, the writer try to conduct research on using this heat rejection from condenser to heating tap water, focusing on water flow rate increased from 0.5 liter/min to 2.5 liter/min. From experiment and analysis result obtained that the maximum heat water temperature which can be reached is 47.5°C in 0.5 liter/min, with the equipment specifications are 2 HP- split air conditioning and the tank volume is 75 liters. The additional result is heating water temperature is fallen when the water flow rate is increased.